An assessment of the chemical and nutritional quality, trypsin inhibitor activity and protein digestibility of soybean products in Nigeria - Adeleye, O.O.; Oyeniyi, T.M. (Nigerian Journal of Animal Science, 2023)
The varied processing protocols used to process soybean results in soybean products with a variety of nutritional properties and anti-nutritional components, hence this study was conducted to evaluate the nutritional properties and residual trypsin inhibitor content of soybean products processed in Nigeria. Soybean products (soybean meal and full fat soy meal) were sourced from processing plants across Nigeria and assayed for their crude protein content. Based on their crude protein content, soybean products were classified as either low protein (44-46% crude protein), “type 48” (47-49% crude protein), “type 50” soybean meal (≥ 50% crude protein), or full fat meals (< 40%). They were further assayed for moisture, ether extract, crude fibre, ash, gross energy, amino acid profile, trypsin inhibitor activity, protein dispersibility index (PDI), KOH protein solubility and in vitro protein digestibility, and metabolizable energy for poultry was estimated. This study showed that “type 50” soybean meal was significantly highest in crude fibre (7.33 ± 0.71%), moisture (11.42 ± 0.21%), and ash (7.97 ± 0.50%), ”type 48” soybean meals were significantly higher in in vitro protein digestibility (49.15 ± 6.26%), while full fat meals were significantly higher in ether extract (18.01 ± 0.54%), Gross energy (5.28 ± 0.007 kcal/g) and trypsin inhibitor activity (9.20 ± 1.57 TIU mg/g). While only the “Type 50” soybean meals were within the tolerance range for trypsin inhibitors [4 mg/g] in broiler chickens. This study has provided baseline data for the variability that could be expected for soybean products originating from Nigeria.